2019
DOI: 10.1155/2019/1703842
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Expression Levels of a Panel of Genes (IRF5, STAT4, TNFSF4, MECP2, and TLR7) and Cytokine Levels (IL-2, IL-6, IL-10, IL-12, IFN-γ, and TNF-α) with Systemic Lupus Erythematosus Outcomes in Jordanian Patients

Abstract: Systemic lupus erythematosus (SLE) is characterized by systemic end-organ damage. We investigated the involvement of IRF5, TLR-7, MECP2, STAT4, and TNFSF4 genes and TNF-α, IFN-γ, IL-2, IL-12, IL-6, and IL-10 cytokines in SLE pathogenesis and in organ damage in Jordanian patients. Blood was collected from 51 patients and 50 controls. Expression levels of SLE genes in PBMCs and cytokine levels were determined using RT-PCR and ELISA, respectively. Expression levels of all genes and levels of TNF-α, IL-12, IL-6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“… 19 Furthermore, higher levels of STAT4 expression have demonstrated association with increased cardiovascular damage in patients with SLE. 30 To investigate whether smoking also increases the levels of pSTAT4, we analysed IL-12 stimulated CD8+ T cells from healthy blood donors who were smokers (n=20) or never-smokers (n=25). We found the levels of pSTAT4 to be higher in smokers (p=0.0063), with a mean value of 1063 compared with 565 in non-smokers ( figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Furthermore, higher levels of STAT4 expression have demonstrated association with increased cardiovascular damage in patients with SLE. 30 To investigate whether smoking also increases the levels of pSTAT4, we analysed IL-12 stimulated CD8+ T cells from healthy blood donors who were smokers (n=20) or never-smokers (n=25). We found the levels of pSTAT4 to be higher in smokers (p=0.0063), with a mean value of 1063 compared with 565 in non-smokers ( figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“… 33 When STAT4 is activated and phosphorylated, it homodimerises and translocates to the nucleus where it induces expression of hundreds of genes, resulting in production of IFN-γ, T-helper type 1 and 17 differentiation and activation of monocytes. 34 Increased STAT4 mRNA expression is associated with increased cardiovascular damage in patients with SLE, 30 and several studies on animal models indicate a link between STAT4 and the development of atherosclerosis. 35 The mechanism of how smoking leads to increased levels of activated STAT4 is unclear, however, we speculate that epigenetics may constitute the bridge between smoking, genetics and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that IL-12 levels are increased in SLE patients (Uzrail et al, 2019[ 190 ]; Zhou et al, 2019[ 222 ]; Guimarães et al, 2017[ 72 ]) and that risk loci for IL12RB (You et al, 2015[ 215 ]) and genetic variants of IL12B (Paradowska-Gorycka et al, 2016[ 149 ]) are associated with SLE. On the other hand, however, it has been shown that there is a T H 17/T reg imbalance in patients with SLE (Talaat et al, 2015[ 179 ]) as well as a shift in the T H 1/T H 2 balance towards T H 2 cytokines (Uzrail et al, 2019[ 190 ]), suggesting that IL-12 is one cytokine among others in disease pathogenesis.…”
Section: Relevance Of Il-12 In Different Diseases and Disease Modelsmentioning
confidence: 99%
“…8 Many authors have highlighted an increase in SLE patients of all the above-mentioned putative factors contributing to vasogenic oedema of PRES, particularly in the active phase of the disease. 9 Notably, even in pre-eclampsia and eclampsia, there is a deregulation of cytokines and leucocyte activity. 10…”
mentioning
confidence: 99%